The Routledge international handbook of economic sociology - Zafirovski, Milan 1958- (Routledge, 2023)
"This handbook presents a systematic and comprehensive overview of economic sociology, an exemplary interdisciplinary field which draws on theoretical frameworks and empirical findings from both economics and sociology to present a unique lens on the interdependence of the economy and society. The handbook is arranged in four parts which together present the current state-of-the-art of economic sociology as well as pointing towards future directions for research. The first part outlines the theoretical foundations of economic sociology and its relations to other fields, particularly with regard to other alternative approaches to economics, and looks at conceptions and definitions of economic sociology vary. The second part provides an overview of the historical development of economic sociology from classical political economy to the present day. The third part explores the main problematics of economic sociology, analyzing the economy in relation to particular social institutions, the state, ideology, culture and art, religion, gender, race/ethnicity, and more. The fourth part focuses on the principal branches of including sociology of the market, industrial organization and work, uncertainty, distribution and inequality, money and finance, and the environment. The stellar international cast of contributors is drawn from both economics and sociology therefore presenting a holistic view of the field and contributing to a rejuvenation of economic sociology within economics. It is an indispensable reference work for researchers and students across a broad range of sociological and economic disciplines"
Includes bibliographical references and index
Keywords: Wirtschaftssoziologie; Economics / Sociological aspects; Aufsatzsammlung